A study on Cold-formed Steel Frame Connection: A review - Komara, Indra; Wahyuni, Endah; Suprobo, Priyo (IPTEK The Journal for Technology and Science, 2025)
This paper is aimed to review the current researches on Cold-formed steel (CFS) structures, particularly for screw connections, welded connections, bolted connections and adhesive connections. Connection presents as a major parameter of the important elements for CFS framing system in order to attain its structural stability. The performance of different CFS connections is well-discussed in order to capture the behaviour of each type of connection. Based on the review assessment, the results highlighted that all types of connections except adhesive connections have shown the proper behaviour that can trigger the change of any design codes. Otherwise, adhesive connection is given several advantages that leads a novelty in the construction technology. Hence it still has some gaps of knowledge that are needed to be filled with comprehensive future researches.